Notes about the floristic diversity in the Triglav National Park and the vascular flora of the towns of Budva, Podgorica and Dubrovnik (Adriatic Coast of Croatia and Montenegro) - Dimitar Dimitrov; Vasil Vutov (Historia naturalis bulgarica, 2017)
This article describes the flora of the northern slopes of the Triglav Peak (Julian Alps). Further, we discuss the flora of Dubrovnik (the old town area) and the flora of the towns of Budva and Podgoritsa.